Severe infective keratitis leading to hospital admission in New Zealand. Issue 9 (20th August 2003) - Wong, T; Ormonde, S; Gamble, G; McGhee, C N J
Abstract : Aim: To identify key risk factors and the management and outcome of severe infective keratitis leading to public hospital admission in New Zealand. Methods: Over a 2 year period, all admissions of presumed infective keratitis to Auckland Hospital were identified. The clinical records of all 103 cases were retrospectively reviewed with respect to clinical features, risk factors, management, and outcomes. Results: The mean time from first symptoms or signs and presentation to hospital was 8.9 (SD 15.5) days. The majority of subjects, 88%, had at least one of the risk factors commonly associated with infective keratitis including previous ocular surgery (30%), contact lens wear (26%), topical corticosteroid use (25%), and ocular trauma (24%). Corneal scraping was performed in 92% and of a total of 105 scrapes, 71% were positive. Bacteria were isolated in all these cases, the majority being Gram positive organisms (72%). The most common isolates identified were coagulase negative Staphylococcus (16%), Propionibacterium acnes (14%), Staphylococcus epidermidis (11%), and Streptococcus pneumoniae (9%). In addition, yeasts were isolated in 5%, fungi in 4%, virus in 2%, and chlamydia in 1%. Importantly, polymicrobial infection accounted for 33% of culture positive cases. Antimicrobial treatment was changed on the basis of culture results in 17 cases (16.5%). Median initial visual and final best corrected visual acuity was 6/36–6/48 (logMAR 0.86) (IQR 0.39–2.00) and 6/12–6/15 (logMAR 0.360) (IQR 0.15–1.70), respectively. Previous ocular surgery and topical corticosteroid use were significantly associated with poorer visual acuity. The mean hospital stay was 5.8 days and the median 4.0 (IQR 2.0–8.0) days. Longer duration of stay was associated with the presence of hypopyon, larger ulcers, previous ocular surgery, and poor visual acuity. Conclusions: Infectious keratitis is an important cause of ocular morbidity. A significant proportion of cases have potentially modifiable risk factors. Previous ocular surgery and topical corticosteroid use, in particular, were associated with poorer visual outcomes. Many cases of severe keratitis might be avoided, or their severity reduced, by appropriate education of patients and ophthalmologists.